Peningkatan Pengetahuan Geotermal pada Siswa di Daerah Lingkar Wisata Geotermal Lombongo - Intan Noviantari Manyoe; Dela Pusfika Sari Napu; Siti Suhartini S. Napu (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2021)
Geothermal is a type of renewable energy whose utilization can be applied in the tourism sector. This community service aims to increase geothermal knowledge and knowledge about the hazards that can be caused so that students have a basic understanding of geothermal and can minimize the risks or hazards generated by geothermal if students visit geothermal tourism objects. The implementation method is in the form of geothermal learning through the provision of material with interesting handouts and geothermal songs. The results of the community service show that students have basic knowledge of geothermal and have the ability to protect themselves if they are around hot springs.